Estudo comparativo do esgarçamento em tecidos de cetim 100% poliéster e cetim 97% poliéster/3% poliuretano em uma costura tipo 301 - Silva, Pedro Henrique da (2023)
Satin is a flat fabric known for its satin sheen and soft touch, but due to its structure and composition it is a very delicate fabric and if not handled correctly it can present various defects such as fraying of the seam. This research aimed to analyze fraying in fabrics with the same pattern as satin with different fibrous compositions, using sewing parameters-type 301 of the clothing industry. To carry out the experiment, satin samples with different densities of stitches were sewn, then submitted to the traction test in the dynamometer. The results showed that the decrease in the density of stitches type 301 alters the performance of resistance to fraying, in which satin 97% polyester and 3% elastane presented greater resistance to fraying when compared to the same type of sewing in a satin 100 % polyester. Thus, it was possible to conclude that the fibrous composition of the satin fabric interferes with the resistance to fraying for the same sewing conditions with stitch type 301 and density of 5 stitches per centimeter.